Adenovirus serotypes isolated from ocular infections in London. Issue 2 (February 1983) - Darougar, S; Walpita, P; Thaker, U; Viswalingam, N; Gardner, L; McSwiggan, D A
Abstract : During the period 1973-8 700 adenoviruses were isolated from the eyes of patients presenting at Moorfields Eye Hospital. Of these, 678 were serotyped by a neutralisation test. Twenty-one different serotypes were identified. Serotype 3, 7, and 10 accounted for 68% of the isolates, 4, 8, 15 (15/29), and 19 for 25%, and the other 14 serotypes for 7%. Community outbreaks of ocular infections by adenovirus 3, 4, 7, 10, and 15 (15/29) were observed. Outbreaks with adenovirus 3, 7, and 10 appeared to continue for 2 years or more, whereas outbreaks with 4 and 15 (15/29) were restricted to one year or less. Hospital outbreaks by adenovirus 8 and 19 were also recorded. During the same period 18 of these 21 adenovirus serotypes were isolated from the nonocular sites (mainly respiratory tract) in 7804 cases. There was a close association in the distribution of adenovirus 1, 2, 3, 5, and 6 in the ocular and nonocular sites. No such association was observed for adenovirus serotypes 4, 8, 10, 15 (15/29), and 19.